Impact of electrode orientation, myocardial wall thickness, and myofiber direction on intracardiac electrograms: numerical modeling and analytical solutions - Leenknegt, Lore; Panfilov, Alexander V.; Dierckx, Hans (Frontiers in Physiology, 2023)
abstract Intracardiac electrograms (iEGMs) are time traces of the electrical potential recorded close tothe heart muscle. We calculate unipolar and bipolar iEGMs analytically for a myocardial slab with parallel myofibers and validate against numerical bidomain simulations. The analytical solution obtained via the method of mirrors is an infinite series of arctangents. It goes beyond the solid angle theory and is in good agreement with the simulations, even though bath loading effects were not accounted for in the analytical calculation. At large distance from the myocardium, the iEGMs decay as 1/R (unipolar), 1/R^2 (bipolar, parallel) and 1/R^3 (bipolar, perpendicular to the endocardium). At the endocardial surface, there is a mathematical branch cut. We show how thicker myocardium generates iEGMs with larger amplitude and how anisotropy affects the iEGM width and amplitude. If only the leading order term of our expansion is retained, it is found how the conductivities of the bath, torso and myocardium as well as myofiber direction together determine the iEGM amplitude. Our results will be useful for the quantitative interpretation of iEGMs, the selection of thresholds to characterise viable tissue, as well as future inference of tissue parameters. Keywords: Bidomain, EGM, modeling, Simulations, openCARP, solid angle abstract